Assembly/Disassembly of DNA-Au Nanoparticles: A Strategy of Intervention. (13th February 2008) - Lim, I-Im S.; Wang, Lingyan; Chandrachud, Uma; Gal, Susannah; Zhong, Chuan-Jian
Abstract : This report describes the viability of a strategy for manipulating the assembly/disassembly processes of DNA-Au nanoparticles by molecular intervention. Using the temperature-induced assembly and disassembly processes of DNAs and gold nanoparticles as a model system, the introduction of a molecular recognition probe is demonstrated to lead to the intervention of the assembly/disassembly processes depending on its specific biorecognition. This process can be detected by monitoring the change in the optical properties of gold nanoparticles and their DNA assemblies. Implications of the preliminary results to exploration of the resulting nanostructures for fine-tuning of the interfacial reactivities in DNA-based bioassays and biomaterial engineering are also discussed.